Inter-cluster and intra-cluster flow distribution and proppant allocation in deep coalbed methane orientation fracturing - Ruiyue YANG; Yiwen LIU; Yu LI; Mengmeng ZHOU; Yanjin GONG; Zhongwei HUANG (Meitan xuebao)
China has abundant deep coalbed methane (CBM) resources with significant potential for development and utilization, which is expected to become an important supplement to national natural gas supply. However, the current deep CBM development technology is still in the exploratory status, and the reservoir stimulation mainly relies on massive fracturing, which suffers from significant differences in gas production rate and rapid production declines. The major reason behind is the lack of a stimulation technology that precisely matches geological conditions. “Orientation perforating + targeted fracture controlling + precision fracturing” is expected to become an effective fracturing method that is geologically compatible with deep CBM. This paper proposes seven orientation perforating patterns for deep coalbed horizontal wells: directional horizontal, 4 o’clock—8 o’clock orientation downward, fan-shaped orientation downward (upward), fan-shaped orientation downward (upward) + horizontal (240° perforation pattern), and straight upward orientation (downward). To investigate the uniformity of fluid and proppant distribution between and within clusters in deep coalbed horizontal wells under different orientation perforating patterns, this paper utilizes a coupled computational fluid dynamics and discrete element method (CFD-DEM). A fluid-particle transport fluid-solid coupling model for horizontal wellbores is established. The study examines the characteristics of inter-cluster and intra-cluster flow distribution and proppant distribution under different orientation perforating patterns, flow rates, sand ratios, cluster numbers within one stage, and graded proppant injection. The results show that the uniformity of flow and proppant distribution varies under different orientation perforating methods. The 240° orientation perforating (fan shape down or up + horizontal direction) shows better uniformity in flow distribution between holes, and the 240° orientation perforating and 4 o’clock—8 o’clock orientation downward perforating show better uniformity in proppant distribution between holes. High pumping rates (> 16 m3/min), low sand ratios (maximum sand ratio during the sand carrying stage < 25%), a higher proportion of smaller particle-sized proppants (0.212/0.109 mm∶0.380/0.212 mm∶0.550/0.270 mm = 6∶3∶1), and 3 to 4 clusters within a stage are conducive to the uniform distribution of flow and proppant between holes/clusters, enhancing the balance of reservoir stimulation. Field applications in the eastern margin of the Ordos Basin for deep CBM have shown that orientation perforating yields higher gas production than conventional spiral perforating, with the “fan shape down + horizontal direction (240° pattern)” orientation perforating showing the most significant increasing in gas production. It is recommended that deep CBM reservoir stimulation be designed based on the position of the well trajectory within the coal seam (especially its relative position to bright coal), implementing a “one-cluster one-policy” perforating design to induce directional fracture initiation, targeted communication with the “geological-engineering” sweet spots, and achieve the stimulation objectives of “directed guidance, taper design, uniform proppant placement and effective support”. The key findings are expected to provide theoretical foundations and parameter references for high-quality and efficient fracturing in deep CBM wells.